PENGARUH LAYANAN KONSELING KELOMPOK DENGAN PENDEKATAN REALITAS TERHADAP PERILAKU PROKRASTINASI AKADEMIK SISWA DI SMP NEGERI 2 O’O’U - Giawa, Lisda Yanti; Rodearni Damanik, Hosianna; Lase, Famahato; Foera-era Lase, Justin (IKIP Siliwangi, 2025)
Academic procrastination is often associated with a form of laziness within the educational context. This issue requires immediate intervention to enable students to minimize, or ideally eliminate, such behavior. This study aims to examine the level of academic procrastination among students at SMP Negeri 2 O’o’u. A quantitative method was employed using a One-Group Pretest-Posttest Experimental Design, involving a single group of participants assessed before and after receiving a treatment. The pretest measured the participants’ initial condition, while the posttest evaluated the impact of the intervention. The sample was selected through purposive sampling, with class XI-B serving as the research subject. Data were collected using an academic procrastination questionnaire and analyzed by comparing pretest and posttest scores. The findings revealed a pretest score of 132.72% and a posttest score of 47.70%, indicating a reduction of 85.03 points. These results demonstrate that group counseling using the reality therapy approach is effective in reducing students’ academic procrastination. When implemented by school counselors following appropriate stages, this intervention tends to yield optimal outcomes.